If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8u + 2u = 3u Combine like terms: 8u + 2u = 10u 10u = 3u Solving 10u = 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 10u + -3u = 3u + -3u Combine like terms: 10u + -3u = 7u 7u = 3u + -3u Combine like terms: 3u + -3u = 0 7u = 0 Divide each side by '7'. u = 0 Simplifying u = 0
| (180/165)=n/(n-2) | | 2x+16=38 | | 8-(4x+7m)=5(x+6)-2 | | 0.40(x+80)+0.80x=68 | | 13x-(4x-6)=60 | | 3/8=2/2 | | -10=-8+6x-2 | | 4-3x=-3x+6 | | f(3)=-2(3)+5 | | 9x+3=17x | | 21x-26=23x-9 | | -5(1+6n)=10 | | -3(3s-3)-9=-2(8s+6)-2 | | Y+20=10(x+9) | | 6x-256=2 | | -4x^2+x-3=0 | | .90x+0.05(6-x)=0.10(71) | | 10n+100-10=600 | | 7x^2+12x=y^2 | | (8/9)×(6/7)= | | 500x+800y=11500 | | .36(18)+.06x=0.12(24+x) | | -24n^10+3n=0 | | 8-3(x-4)=2x+5 | | 22-5x=2x-13 | | 15x-15=-12x | | (8/9)×(6/7) | | v/4-2.1=-8.5 | | 2/3x-2/3 | | 1.5=-7w+12.7 | | 3+2x+2=3x+4 | | -7=-5x-2x+7 |